Netizen's Sharp Satire: Exploring Sarcasm in the Comments Column of the 2024 Presidential Debate on Instagram - Awalia, Afni; Jaja, Jaja; Rosmaya, Elin (Indonesian Journal of Advanced Research, 2025)
In the ever-evolving digital era, social media has become the main means for people to express their opinions. People can express criticism, views, or sarcasm as a form of dissatisfaction or distrust. One phenomenon that attracts attention is the use of sarcasm in the comment section, especially in posts related to the 2024 presidential candidate debate on Instagram. This study aims to analyze the use of sarcasm as a sharp satire by netizens in the comments section of the 2024 presidential candidate debate on Instagram. The research method used is descriptive qualitative method, with data collection techniques through observation of comments on Instagram related to the presidential candidate debate and literature study. The collected data were analyzed through three stages, namely data filtering, data presentation, and conclusion drawing. The results show that sarcasm is used as a tool to express dissatisfaction or belittle the opposing party. Netizens often use sarcasm to satirize presidential candidates or their supporters, with the aim of mocking, ridiculing, or indirectly showing public disapproval. This shows the role of social media in shaping public opinion and how netizens participate in the political process through digital platforms.